Analisis Putusan PN Jayapura Kelas IA, Nomor: 23/Pid.Sus-Anak/2019/PN Jap. Tindak Pidana Penyalahgunaan Narkotika di Kalangan Siswa Menengah Atas - Adhar, Muhammad Hilmi; Nachrawi, Gunawan (Neolectura, 2025)
Drug abuse and illicit trafficking that occurs in the world and in Indonesia has become a frightening problem for the Indonesian people and nation. Narcotics and psychotropic drugs have penetrated all regions of the country and target various levels of society without exception. The impact of narcotics use makes users lack self-confidence and find it difficult to interact socially. The government, schools and parents have an important role in preventing narcotics abuse. The relevant sanction for students who abuse narcotics is rehabilitation, either rehabilitation from the government or independent rehabilitation under government supervision. Through the rehabilitation policy, narcotics abusers, apart from being given treatment to get rid of narcotics, can also be given guidance towards a better life.